Treatment with intravenous immunoglobulin in patients with recurrent pregnancy loss: An update. (June 2019) - Christiansen, Ole B.; Kolte, Astrid M.; Krog, Maria C.; Nielsen, Henriette S.; Egerup, Pia
Highlights: The results of sensitivity analysis of meta-analyses of RCTs in the treatment of recurrent pregnancy loss showing a significant therapeutic effect when treatment is started pre-conception. new data from a follow-up study show that IVIg treatment in a previous pregnancy seems to increase the chance of live birth 10 fold in these patients with an average of 6 previous pregnancy losses. The results of sensitivity analysis of RCTs in the treatment of recurrent pregnancy loss showing a borderline significant effect in patients with secondary recurrent pregnancy loss Abstract: Intravenous immunoglobulin (IVIg) has a documented clinical effect in many autoimmune diseases and has so far been tested in >10 randomised controlled trials (RCTs) in women with recurrent pregnancy loss (RPL). The results of the RCTs have, however, been very divergent. In meta-analyses of all trials, no significant impact on live birth rate has been reported. In contrast, in sensitivity analyses, IVIg significantly increased live birth rates when initiated prior to conception and it had a borderline significant therapeutic effect in women with secondary RPL. Higher dosages of IVIg and serological signs of autoimmunity in the treated patients tended to increase the success rate after treatment. A follow-up study of patients from our recent RCT also supports a significant therapeutic effect in patients who had received IVIg before conception. The lessons learned from the published trials and meta-analyses should be incorporated in the design of future RCTs of IVIg in the treatment of RPL.